(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper aims to exhibit and discuss the outcomes of a major feminist project in Serbia, which lasted from 1998-2004, and resulted in two volumes, including more than 60 authors, under the title “Mapping Misogyny in Serbia: Discourses and Practices” (Vol. I, 2000 and Volume II, 2004). The project started after the defeat of civic protests in 1996-1997, when the civic movement in Serbia became largely discouraged in its efforts to overthrow Milošević, and was conceived and conducted with the purpose to empower and recover the feminist intellectual scene, which was at that time, severely disillusioned about the possibility of positive political and social change. The intellectual aim of the project was to deconstruct misogyny as a cultural practice and a discourse, in very different domains of social life, and at different social levels. The specificity of the project was that it was conceived and carried out as a ‘patchwork’ project in a post-modern sense: it was a multidisciplinary ‘patchwork’ project based on different genres, including essays and academic texts, as well as visual contributions. The nature of the project thus corresponded to the nature of the phenomena in question, misogyny, which takes many different forms. The contributions provided for theoretical steps towards a better understanding of the social phenomenology of misogyny and it created contextualized knowledge about the gender regime in Serbia.